Making Inorganic Chemistry Interesting: Analogy Based Pragmatic Approach to Learning - Rajesh, N. (Resonance, 2020)
The undergraduate student perception of inorganic chemistry as routine and unimaginative was transformed by adopting few innovative approaches in the pedagogy. This is primarily a reflection of my experiences in classroom teaching that is presented in this commentary. Fun-oriented, analogy based and pragmatic approach was used to explain simple concepts in inorganic chemistry. Laboratory demonstrations and exposure to understand research articles made the course more interesting. Selective examples of defining classroom moments are presented in this reflective commentary. Framing questions in an animated, imaginative and unconventional style made students feel quite challenged and also experience the joy in learning. The introduction of group discussion as an evaluative component enhanced the soft skills of the students. The creative instinct in learning changed students’ perception of inorganic chemistry from an insipid to a highly engaging and captivating subject.